ANALISA USABILITY TESTING PADA WEBSITE DESA BANDUNG MENGGUNAKAN METODE SYSTEM USABILITY SCALE - Nurlatifah, Fadila; Anggraeni, Sita (Jurnal Sistem Informasi Kaputama (JSIK), 2024)
The desabandung.id website is an information website managed directly by the Bandung Village government. Based on initial observations of the desabandung.id website, researchers had a little difficulty understanding the initial appearance when they first visited the website. The amount of information presented with such dense content makes it difficult to focus on one thing. We still found website pages with errors and several menus that had no content. Based on these initial observations, the aim of measuring usability on the desabandung.id website is to determine the website display standards according to user requirements. The method that will be used to calculate the level of website usability is the system usability scale method. Data was obtained from filling out questionnaires carried out by 95 respondents as users of the desabandung.id website. The calculation results using the SUS method obtained a value of 77.5. The assessment obtained was that the website received an "Acceptable" range and a Grade C with an "Excellent" rating. This assessment indicates that the desabandung.id website as a whole is well received by users. However, to improve the quality of the website, there are 7 page designs as recommendations for improvement to increase the comfort of website users